6 - The ‘#tag Generation’: Social Media and Youth Participation in the 2019 General Election in Nigeria - Obisesan, Oluwasola Festus (Africa Development, 2022)
This article examines the roles of social media on youth’s political participation in the 2019 General Elections in Nigeria. It interrogates the roles played by these communication tools in the emancipation and agency of youths while revealing the double-edged implications the devices may have on the democratic processes and aspirants. The article employs both primary and secondary methods of data sourcing. Primary data were obtained from in-depth interviews with social media ‘influencers’ who played vital roles during the 2019 General Election in Nigeria. Further, data were obtained from selected social media accounts of prominent politicians and analysed using content analysis. Secondary data were extracted from books, articles, newspapers and magazines. Also, the study was contextualised using use and gratification theory. The study concluded that social media played a vital role in the 2019 General Election in Nigeria. It revealed how social media contributed to citizens’ power and agency through debates and narratives which were instrumental in agenda-setting for the ruling class and citizens’ democratic expectations.